Usia dan obesitas berhubungan terhadap penyakit batu saluran kemih di RSUP Sanglah Denpasar periode Januari 2014 sampai Desember 2014 - Nurfitriani Nurfitriani; Anak Agung Gde Oka (Intisari Sains Medis, 2019)
Introduction: Urinary Stone Disease is the process of forming stones caused by the deposition of a substance with excess amounts of urinary or due to other factors that affect the solvency of substance. Urinary Stone Disease is frequently Â Â found on adults between 15-59 years old. Total patient who diagnosed by Urinary Stone Disease in Indonesia is too high. Many things associated against the onset of this disease, such as age and obesity. Therefore the research to examine which factors cause the occurrence of Urinary Stone Disease is necessary in order to raise the early prevention.Method: Research design is descriptive analytic. Using consecutive sampling method. Data will be analyzed in univariate and bivariate using statistical test of chi-square with a level of significance of Î± < 0.05. Place of research in Sanglah Denpasar Bali Subject of research are men and women above 15 years old, diagnosed with Urinary Stone Disease. Subject research are urology unit visiting patient also patient being hospitalized at Sanglah General Hospital.Result: The research results showed that the age has become risk factors which closely related with Urinary Stone Disease, value of p = 0.002. Obesity does not have significant relations against the occurrence of Urinary Stone Disease with value of p = 0,564.Concluison: Age has close relation with the occurrence of Urinary Stone Disease, while obesity has no relation towards the occurrence of Urinary Stone Disease diseases.